Micrometeorological assessment of sensitivity of canopy resistance to vapour pressure deficit in a Mediterranean oak forest - Pitacco, A; Gallinaro, N (Ann. For. Sci., 1996)
Canopy surface resistance to water vapour (rc) of an extensive Quercus ilex L stand (Bosco Mesola, northeast Italy) has been evaluated by inverting the Penman-Monteith equation. The latent heat flux was estimated by applying the Bowen ratio-energy budget micrometeorological method. A linear relationship was found between rc and the vapour pressure deficit. Canopy resistance increased regularly during the day and that yielded a recurring diurnal pattern of energy partitioning where most of the latent heat was dissipated in the early morning and the release of sensible heat increased after midday. This behaviour has been confirmed also by independent estimates of transpiration, based on measurements of sap flow velocity in small branches. Ecological consequences of this feature are briefly discussed applying the concept of coupling between canopy and atmosphere
Keywords: canopy resistance; energy balance; Evapotranspiration; Quercus ilex L; sap flow